2021
DOI: 10.3390/polym13223994
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of CFRP-Confined Sand-Based Material Columns under Axial Compression

Abstract: This paper presents an innovative pumpable standing support designed for underground mines located in the arid and semi-arid deserts of the Gobi region with a shortage of water resources. The exterior shell of this pumpable standing support is made of carbon fiber-reinforced polymer (CFRP), while the infill material is a sand-based material (SBM). As the novel backfill material, SBM is the combination of high-water cementing material and desert sand. A series of experimental tests were conducted to obtain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that the water–cement ratio and the content of impurities influence HWBMs [ 32 , 33 ]. Guodong Li et al [ 34 , 35 ] used the HWBM from Yangzhou China Mining Construction New Material Technology Co., Ltd. (Yangzhou, China), selected the water–cement ratio of the HWBM to be 1, 1.5 and 2, set the desert sand doping amount to be 0, 30%, and 60%, and made seven types of desert sand-based filling material samples. Through a series of tests, the influence of desert sand-based backfill material on its initial setting time, mechanical properties, microstructure, and the effect of water–cement ratio on the performance of HWBM was studied.…”
Section: Experimental Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the water–cement ratio and the content of impurities influence HWBMs [ 32 , 33 ]. Guodong Li et al [ 34 , 35 ] used the HWBM from Yangzhou China Mining Construction New Material Technology Co., Ltd. (Yangzhou, China), selected the water–cement ratio of the HWBM to be 1, 1.5 and 2, set the desert sand doping amount to be 0, 30%, and 60%, and made seven types of desert sand-based filling material samples. Through a series of tests, the influence of desert sand-based backfill material on its initial setting time, mechanical properties, microstructure, and the effect of water–cement ratio on the performance of HWBM was studied.…”
Section: Experimental Studymentioning
confidence: 99%
“…This material has a high slurry volume after adding water, enabling the desert sand to be better embedded in it. From the microstructure, it can also be seen that when high content of desert sand is added, the compactness of the desert sand-based backfill material is more compact [ 34 ]. Therefore, the high content of desert sand can effectively improve the compressive strength of desert sand-based backfill materials.…”
Section: Analysis Of Influencing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) despite the high content of water, the high-water backfill material is necessary in large quantities [31]; (3) due to the low strength of the backfill body, doping massive cementitious materials enhances the strength [32]. As is well known, aeolian sand extensively occurs on the ground surface in Northwestern China.…”
Section: Introductionmentioning
confidence: 99%